A positive electrode sheet and a lithium ion secondary battery containing the same

By using specific composition active materials and electrolyte additives in the positive electrode sheet of the lithium-ion secondary battery, the problem of forming SEI during the first charging and discharging of lithium-ion secondary batteries is solved, the energy density and cycle life of the battery are improved, and processing difficulty and safety risks are reduced.

CN115136357BActive Publication Date: 2025-03-28NINGDE AMPEREX TECHNOLOGY LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202180010680.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-10-25
Filing Date
2021-11-18
Publication Date
2025-03-28
Estimated Expiration
2041-11-18

AI Technical Summary

Technical Problem

The existing lithium-ion secondary batteries will form a solid electrolyte interface (SEI) during the first charging and discharging process, resulting in irreversible capacity loss and reducing energy density. In addition, the existing positive electrode lithium supplementation method has safety risks and operation difficulties.

Method used

A positive electrode sheet including the first positive electrode active material Li1+xMnyM2-yO4-tAt and the second positive electrode lithium supplement material Li1+rMn1-pNpO2-sBs is used to form a stable SEI layer and an interface protective layer through specific resistance, compaction density and single-side density design, combining the vinylene carbonate and 1,3-propane sulfonate additive in the electrolyte to form a stable SEI layer and an interface protective layer.

Benefits of technology

It improves the energy density, rate performance and cycle life of lithium-ion secondary batteries, reduces the processing difficulty of positive electrode sheets, and improves the safety of the overall battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115136357B_ABST
    Figure CN115136357B_ABST
Patent Text Reader

Abstract

The present application discloses a positive electrode sheet and a lithium-ion secondary battery containing the same. The positive electrode sheet of the present application comprises a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, wherein the positive electrode active material layer comprises a first positive electrode active material Li 1+x Mn y M 2‑y O 4‑t A t and the second positive electrode lithium supplement material Li 1+r Mn 1‑p N p O 2‑s B s , the positive electrode sheet satisfies 1.5≤R·P / Q≤30, where R is the resistance of the positive electrode sheet, in Ω; P is the compaction density of the positive electrode sheet, in g / cm 3 ; Q is the single-sided surface density of the positive electrode sheet, in g / 1540.25mm 2 The surface free lithium content of the second positive electrode lithium supplement material in the positive electrode plate of the present application is very low, and the processing performance is excellent. The lithium-ion secondary battery made from the positive electrode plate of the present application has high energy density, rate performance and cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of batteries and relates to a positive electrode plate and a lithium-ion secondary battery containing the same. Background Art

[0002] During the first charge and discharge process of lithium-ion secondary batteries, a solid electrolyte interface (SEI) will form on the negative electrode surface, causing irreversible capacity loss and reducing the energy density of lithium-ion energy storage devices. In devices using graphite negative electrodes, the first cycle will consume about 10% of the active lithium source; when using negative electrode materials with high specific capacity, such as alloys (silicon, tin, etc.), oxides (silicon oxide, tin oxide), amorphous carbon and other materials, the consumption of active lithium sources will be further aggravated. Therefore, a suitable lithium replenishment method is of great significance to further improve the energy density of lithium-ion secondary batteries.

[0003] Patent CN1427490A proposes a method for replenishing negative electrode lithium, specifically, mixing metal lithium powder, negative electrode material and non-aqueous liquid to form slurry, and coating the slurry on the current collector. This method can improve the energy density of the battery, but the control of moisture in the production process is extremely strict, which increases the difficulty of the process. FMC Company in the United States has made certain improvements to lithium powder, and the stabilized metal lithium powder SLMP (stabled lithium metal powder) produced has better stability, but it can only be stable in dry air for a few hours, which poses a great safety hazard. If the wet method is used, there are also problems with the selection of non-aqueous solvents and the control of moisture.

[0004] In view of the huge challenges faced by the negative electrode lithium replenishment strategy, the relatively safer and easier-to-operate positive electrode lithium replenishment method has received increasing attention from the industry. Patent CN104037418A discloses a positive electrode lithium replenishment material based on lithium oxygen compounds, lithium sources and alkyl lithium, but the decomposition potential of the lithium-containing compound is relatively high, and oxygen and other by-products are produced during the decomposition process, affecting the battery life. Patent CN101877417A discloses Li2NiO2-based lithium replenishment materials. The surface free lithium content of this type of material is extremely high, and it is very easy to cause the slurry to form gel during the slurry mixing process, which seriously affects the processing performance, causes the continuous growth of impedance, and affects the cycle performance. Summary of the invention

[0005] The purpose of the present application is to overcome the deficiencies of the prior art and provide a positive electrode plate and a lithium-ion secondary battery containing the same, aiming to make the positive electrode plate stable, the processing method simple, and the lithium-ion secondary battery have higher energy density, rate performance and cycle life.

[0006] To achieve the above object, in a first aspect, the present application provides a positive electrode plate, which includes a positive electrode current collector and a positive electrode active material layer disposed on at least one surface of the positive electrode current collector, and the positive electrode active material layer includes a first positive electrode active material and a second positive electrode lithium supplementing material; the positive electrode plate satisfies 1.5 ≤ R·P / Q ≤ 30, where R is the resistance of the positive electrode plate in Ω; P is the tap density of the positive electrode plate in g / cm 3 ; Q is the single-sided areal density of the positive electrode plate in g / 1540.25mm 2 .

[0007] Preferably, the first positive electrode active material is Li 1+x Mn y M 2-y O 4-t A t , where -0.1 < x < 0.2, 1 < y ≤ 2, 0 ≤ t < 0.5, M is at least one of Ni, Fe, Zn, Mg, Al, Ti, Zr, and A is at least one of S, N, F, Cl, Br.

[0008] Preferably, the second positive electrode lithium supplementing material is Li 1+r Mn 1-p N p O 2-s B s , where -0.1 < r < 0.2, 0 ≤ p < 0.2, 0 ≤ s < 0.2, N is at least one of Fe, Co, Ni, Ti, Zn, Mg, Al, V, Cr, Zr, and B is at least one of S, N, F, Cl, Br.

[0009] Preferably, the positive electrode plate satisfies at least one of the following characteristics:

[0010] (a) The positive electrode plate satisfies 3.0 ≤ R·P / Q ≤ 15;

[0011] (b) The R ≤ 5 Ω, preferably the R ≤ 2 Ω;

[0012] (c) The P satisfies 2.5 g / cm 3 < P < 3.2 g / cm 3 ;

[0013] (d) The Q satisfies 0.3 g / 1540.25mm 2 < Q < 0.55 g / 1540.25mm 2 .

[0014] Preferably, the weight ratio of the first positive electrode active material to the second positive electrode lithium replenishing material is first positive electrode active material: second positive electrode lithium replenishing material = 5: 1 to 99: 1. More preferably, the weight ratio of the first positive electrode active material to the second positive electrode lithium replenishing material is first positive electrode active material: second positive electrode lithium replenishing material = 9: 1 to 99: 1.

[0015] Preferably, the weight content of the first positive electrode active material in the positive electrode active material is 80% to 98%. More preferably, the weight content of the first positive electrode active material in the positive electrode active material is 85% to 98%.

[0016] In a second aspect, the present application provides a lithium-ion secondary battery, which includes the positive electrode plate, the negative electrode plate, the isolation membrane and the electrolyte.

[0017] Preferably, the electrolyte comprises the following components in percentage by weight: 0.001% to 5% of vinylene carbonate, and / or 0.001% to 5% of 1,3-propane sultone.

[0018] Compared with the prior art, the beneficial effects of the present application are as follows: the surface free lithium content of the second positive electrode lithium supplement material in the positive electrode plate of the present application is very low, the slurry stability is good, and the processing performance is excellent. Moreover, under the synergistic effect of the first positive electrode active material and the second positive electrode lithium supplement material, and the positive electrode plate is limited to satisfy 1.5≤R·P / Q≤30, the obtained lithium ion secondary battery has a higher energy density, rate performance and cycle life. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the XRD spectrum of the second positive electrode lithium replenishing material in Example 1 before and after the first cycle of charging, wherein Figure b is a partial enlarged view of Figure a.

[0020] Figure 2 This is the first cycle charge and discharge curve of the second positive electrode lithium supplement material in Example 1. DETAILED DESCRIPTION

[0021] In order to better illustrate the purpose, technical solutions and advantages of the present application, the present application will be further described below in conjunction with specific embodiments. Those skilled in the art should understand that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.

[0022] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.

[0023] Positive electrode:

[0024] The positive electrode sheet of the present application includes a positive current collector and a positive active material layer provided on at least one surface of the positive current collector. As an example, the positive current collector includes two opposite surfaces in its own thickness direction, and the positive active material layer is provided on any one or both of these two surfaces.

[0025] In the positive electrode sheet of the present application, the positive active material layer includes a first positive active material and a second positive lithium supplement material; the positive electrode sheet satisfies 1.5 ≤ R·P / Q ≤ 30, where R is the resistance of the positive electrode sheet, in units of Ω; P is the tap density of the positive electrode sheet, in units of g / cm 3 ; Q is the single-sided areal density of the positive electrode sheet, in units of g / 1540.25mm 2 .

[0026] The first positive active material is Li 1+x Mn y M 2-y O 4-t A t , where -0.1 < x < 0.2, 1 < y ≤ 2, 0 ≤ t < 0.5, M is at least one of Ni, Fe, Zn, Mg, Al, Ti, Zr; A is at least one of S, N, F, Cl, Br.

[0027] The second positive lithium supplement material is Li 1+r Mn 1-p N p O 2-s B s , where -0.1 < r < 0.2, 0 ≤ p < 0.2, 0 ≤ s < 0.2, N is at least one of Fe, Co, Ni, Ti, Zn, Mg, Al, V, Cr, Zr; B is at least one of S, N, F, Cl, Br.

[0028] The positive electrode plate of the present application adopts a first positive electrode active material and a second positive electrode lithium supplement material of a specific composition, wherein the first positive electrode active material has a stable structure, good cycle stability and a high first coulomb efficiency; the second positive electrode lithium supplement material has a low free lithium content on the surface and excellent processing performance. Compared with the first positive electrode active material, the second positive electrode lithium supplement material has a higher first charge specific capacity and a lower first discharge specific capacity, that is, the first coulomb efficiency is low. During the first charge, the second positive electrode lithium supplement material can release a large amount of lithium ions to make up for the loss of active lithium caused by the formation of SEI. During the first discharge, there are enough lithium ions back embedded in the first positive electrode active material to improve the energy density of the battery. Under the synergistic effect of the first positive electrode active material and the second positive electrode lithium supplement material, the energy density, rate performance and cycle life of the lithium ion secondary battery are effectively improved. Compared with the combination of the first positive electrode active material and the second positive electrode active material in the patent CN110265627A we applied for before, the combination of the first positive electrode active material and the second positive electrode lithium supplement material used in the present application can more significantly improve the energy density, rate performance and cycle life of the lithium ion secondary battery. At the same time, the present application specifically designs the resistance R, compaction density P and single-sided surface density Q of the positive electrode sheet, which can further improve the energy density, rate performance and cycle life of the lithium-ion secondary battery, and achieve the organic unity of high energy density, good rate performance and long cycle life.

[0029] In order to achieve the function of replenishing lithium, the second positive electrode replenishing lithium material in the present application must satisfy 1-p>0.8 (i.e. 0≤p<0.2). Specifically, the second positive electrode replenishing lithium material in the present application has two phase structures, which belong to the Pmmn and C2 / m space groups respectively. The Pmmn space group corresponds to the characteristic diffraction peak A appearing at 15° to 16° in its X-ray diffraction spectrum, and the C2 / m space group corresponds to the characteristic diffraction peak B appearing at 18° to 19° in its X-ray diffraction spectrum. The intensity I of the characteristic diffraction peak A is A and the intensity I of the characteristic diffraction peak B B The ratio I A / I B Satisfy 0 A / I B ≤0.2. After the first cycle of charging, the characteristic diffraction peak A and the characteristic diffraction peak B both shifted to the low angle direction, and the shift amplitude was <0.5°.

[0030] ​In the present application, the positive electrode plate must satisfy 1.5≤R·P / Q≤30 to ensure that the lithium-ion secondary battery has a higher energy density, rate performance and cycle life. In certain embodiments of the present application, R·P / Q is a value among 1.5, 3, 6, 9, 12, 15, 18, 21, 24, 27, 30, etc. In some preferred embodiments of the present application, R·P / Q satisfies 3.0≤R·P / Q≤15, so that the resulting lithium-ion secondary battery has a longer cycle life and rate performance, such as R·P / Q is a value among 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, etc.

[0031] In this article, the calculation of R·P / Q only involves numerical calculations. For example, the resistance R of the positive electrode is 1.0Ω and the compaction density P is 3.0g / cm 3 The single-sided surface density Q of the positive electrode is 0.35g / 1540.25mm 2 , then R·P / Q=8.57.

[0032] The resistance R of the positive electrode is the resistance value measured by the DC two-probe method, where the contact area between the probe and the positive electrode is 49πmm 2 During the research process of this application, the resistance R of the positive electrode sheet was tested using a Hioki BT23562 internal resistance tester. The specific operation was as follows: the upper and lower sides of the positive electrode sheet were clamped between the two conductive terminals of the tester, and pressure was applied to fix it. The diameter of the conductive segment was 14 mm, and the applied pressure was 15 MPa to 27 MPa, and the resistance R of the positive electrode sheet was measured.

[0033] The compaction density P of the positive electrode sheet can be calculated by the formula P = m / v, where m is the weight of the positive electrode active material layer in g; v is the volume of the positive electrode active material layer in cm 3 The volume v of the positive electrode active material layer can be the area A of the positive electrode active material layer. r The product of the thickness of the positive electrode active material layer.

[0034] The single-sided surface density Q of the positive electrode sheet can be obtained by the formula Q = 1540.25m / A r Calculation shows that, where m is the weight of the positive electrode active material layer, in g; A r is the area of ​​the positive electrode active material layer, in mm 2 .

[0035] It should be pointed out that the sheet resistance R, compaction density P and single-sided surface density Q of the positive electrode are key parameters in the design and production of lithium-ion secondary batteries. If the sheet resistance R of the positive electrode is too large, the cycle performance and rate performance of the lithium-ion secondary battery will be deteriorated. If the compaction density P is too large or too small, the cycle performance and rate performance of the lithium-ion secondary battery will deteriorate. If the single-sided surface density Q of the positive electrode is too large, the cycle life of the lithium-ion secondary battery will be reduced, and it will also affect the penetration of the electrolyte, thereby affecting the rate performance of the battery, especially reducing the discharge capacity of the battery at high rates; and if the single-sided surface density Q of the positive electrode is too small, it means that under the same battery capacity, the length of the current collector and the diaphragm increases, increasing the ohmic internal resistance of the battery. This requires that these parameters can be comprehensively designed in the production of the battery to ensure that the positive electrode reaches the expected design value, so that the electrochemical performance of the lithium-ion secondary battery can achieve the expected results.

[0036] The sheet resistance R of the positive electrode sheet is preferably R≤5Ω, so as to improve the cycle performance and rate performance of the lithium-ion secondary battery. The sheet resistance R of the positive electrode sheet is more preferably R≤2Ω, so as to further improve the cycle performance and rate performance of the lithium-ion secondary battery.

[0037] The compaction density P of the positive electrode sheet is preferably 2.5 g / cm 3 <P<3.2g / cm 3 , which is beneficial to the migration of electrons and ions in the positive electrode, thereby improving the cycle performance of lithium-ion secondary batteries.

[0038] The single-sided surface density Q of the positive electrode sheet is preferably 0.3g / 1540.25mm 2 <Q<0.55g / 1540.25mm 2 , which can improve the cycle performance and rate performance of lithium-ion secondary batteries while ensuring the charge and discharge capacity.

[0039] The weight ratio of the first positive electrode active material to the second positive electrode lithium supplement material is preferably 5:1 to 99:1. The majority of the positive electrode sheet is the first positive electrode active material, which has higher structural stability, can reduce the capacity loss and impedance increase caused by the structural damage of the positive electrode active material, and maintain the cycle stability and kinetic performance. The weight ratio of the first positive electrode active material to the second positive electrode lithium supplement material is more preferably 9:1 to 99:1 to further improve the cycle stability and kinetic performance.

[0040] The weight content of the first positive electrode active material in the positive electrode active material is 80% to 98%, more preferably 85% to 98%.

[0041] The positive electrode sheet of the embodiment of the present application may further include a conductive agent and a binder in the positive electrode active material layer. The present application does not specifically limit the types of the conductive agent and the binder, and they may be selected according to actual needs.

[0042] As an example, the conductive agent can be at least one of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, carbon nanofibers, etc.; the binder can be at least one of styrene-butadiene rubber (SBR), waterbased acrylic resin, carboxymethyl cellulose (CMC), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), ethylene-vinyl acetate copolymer (EVA), polyvinyl alcohol (PVA), etc.

[0043] In some optional embodiments, the weight percentage of the conductive agent in the positive electrode active material layer is ≥ 0.5%, so as to obtain a lower positive electrode film resistance.

[0044] In some optional embodiments, the weight percentage of the binder in the positive electrode active material layer is ≤2.0%, so as to obtain a lower positive electrode film resistance.

[0045] The positive electrode current collector may be a metal foil or a porous metal plate, for example, a foil or a porous plate formed of a metal such as aluminum, copper, nickel, titanium, silver, or an alloy thereof, such as aluminum foil.

[0046] The thickness of the positive electrode current collector is preferably 5 μm to 20 μm, more preferably 6 μm to 18 μm, and even more preferably 8 μm to 16 μm.

[0047] Lithium-ion secondary battery:

[0048] The positive electrode plate of the present application can be used as the positive electrode of a lithium-ion secondary battery. The lithium-ion secondary battery comprises a positive electrode plate, a negative electrode plate, a separator and an electrolyte, wherein the positive electrode plate adopts the positive electrode plate of the present application. Due to the use of the positive electrode plate of the present application, the lithium-ion secondary battery of the present application has high energy density, cycle performance and rate performance at the same time.

[0049] The negative electrode plate may be a metal lithium plate, or may include a negative electrode current collector and a negative electrode active material layer disposed on at least one surface of the negative electrode current collector.

[0050] The negative electrode active material layer generally includes a negative electrode active material, a conductive agent, a binder and a thickener. As an example, the negative electrode active material can be natural graphite, artificial graphite, mesophase microcarbon beads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO, Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel structure lithium titanate Li4Ti5O12 , Li-Al alloy, metallic lithium, etc.; the conductive agent can be at least one of graphite, superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, carbon nanofibers, etc.; the binder can be at least one of styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl butyral (PVB), water-based acrylic resin, carboxymethyl cellulose (CMC), etc.; the thickener can be carboxymethyl cellulose (CMC), etc. However, the present application is not limited to these materials, and the present application can also use other materials that can be used as negative electrode active materials, conductive agents, binders and thickeners for lithium-ion secondary batteries.

[0051] The negative electrode current collector may be made of a metal foil or a porous metal plate, for example, a foil or a porous plate made of a metal such as copper, nickel, titanium, iron, or an alloy thereof, such as copper foil.

[0052] The negative electrode sheet can be prepared according to conventional methods in the art. Usually, the negative electrode active material and optional conductive agent, binder and thickener are dispersed in a solvent to form a uniform negative electrode slurry, and the solvent can be N-methylpyrrolidone (NMP) or deionized water. The negative electrode slurry is coated on the negative electrode current collector, and the negative electrode sheet is obtained through drying, cold pressing and other processes.

[0053] There is no limitation on the above-mentioned isolation membrane, and any known porous structure isolation membrane with electrochemical stability and chemical stability can be selected, such as a single-layer or multi-layer film of at least one of glass fiber, non-woven fabric, polyethylene (PE), polypropylene (PP), and polyvinylidene fluoride (PVDF).

[0054] The electrolyte includes an organic solvent, an electrolyte lithium salt and an additive. The present application does not impose any specific restrictions on the types of the organic solvent and the electrolyte lithium salt, and they can be selected according to actual needs.

[0055] As an example, the above-mentioned organic solvent can be at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), cyclopentane sulfone (SF), dimethyl sulfone (MSM), methyl ethyl sulfone (EMS), diethyl sulfone (ESE), etc., and preferably two or more.

[0056] The above-mentioned electrolyte lithium salt can be at least one of LiPF6 (lithium hexafluorophosphate), LiBF4 (lithium tetrafluoroborate), LiClO4 (lithium perchlorate), LiAsF6 (lithium hexafluoroarsenate), LiFSI (lithium bis(fluorosulfonyl)imide), LiTFSI (lithium bis(trifluoromethanesulfonyl)imide), LiTFS (lithium trifluoromethanesulfonate), LiDFOB (lithium difluorooxalatoborate), LiBOB (lithium dioxalatoborate), LiPO2F2 (lithium difluorophosphate), LiDFOP (lithium difluorobis(oxalatophosphate), LiTFOP (lithium tetrafluorooxalatophosphate), etc.

[0057] The electrolyte additive includes vinylene carbonate (VC), and the weight content of the vinylene carbonate is 0-5% based on the total weight of the electrolyte and is not 0. By adding the vinylene carbonate additive to the electrolyte, a more uniform and dense SEI film is formed at the negative electrode, which inhibits the continuous loss of active lithium.

[0058] The electrolyte additive includes 1,3-propane sultone (PS), and the weight content of the 1,3-propane sultone is 0-5% and not 0 based on the total weight of the electrolyte. By adding 1,3-propane sultone to the electrolyte, an interface protection layer is formed on the positive electrode side, which can further improve the cycle life of the lithium-ion secondary battery.

[0059] The electrolyte may also optionally include other additives, which may be any additive that can be used as a lithium-ion secondary battery. The present application does not impose any specific restrictions and may be selected according to actual needs. As an example, the additive may also include at least one of vinyl ethylene carbonate (VEC), succinonitrile (SN), adiponitrile (AND), 1,3-propylene sultone (PST), sulfonate cyclic quaternary ammonium salt, tris(trimethylsilyl) phosphate (TMSP), and tris(trimethylsilyl) borate (TMSB).

[0060] The above-mentioned electrolyte can be prepared according to conventional methods in the art. An organic solvent, an electrolyte lithium salt, vinylene carbonate, 1,3-propane sultone and other optional additives can be mixed evenly to obtain an electrolyte, wherein the order of adding each material is not particularly limited. For example, an electrolyte lithium salt, vinylene carbonate, 1,3-propane sultone and other optional additives are added to an organic solvent and mixed evenly to obtain an electrolyte. Among them, the electrolyte lithium salt can be first added to the organic solvent, and then vinylene carbonate, 1,3-propane sultone and other optional additives are added to the organic solvent separately or simultaneously.

[0061] The positive electrode sheet, the separator and the negative electrode sheet are stacked in order, and the separator is placed between the positive electrode sheet and the negative electrode sheet to play an isolating role, to obtain a battery cell, or the battery cell can be obtained by winding; the battery cell is placed in a packaging shell, and the electrolyte is injected and sealed to obtain a lithium-ion secondary battery.

[0062] During the research process, the following methods were used to test the charge and discharge curves, high temperature cycle performance and rate performance of lithium-ion secondary batteries:

[0063] Charge and discharge curve test: At 45°C, charge the lithium-ion secondary battery at a constant current of 0.1C to 4.3V, then charge at a constant voltage to a current less than or equal to 0.025C, and then discharge at a constant current of 0.1C to 3.0V, and record the charge and discharge curve of the lithium-ion secondary battery.

[0064] High temperature cycle performance test: At 45°C, charge the lithium-ion secondary battery to 4.3V at a constant current of 1.5C, then charge at a constant voltage until the current is less than or equal to 0.05C, and then discharge at a constant current of 1C to 3.0V. This is a charge and discharge cycle, and record the discharge capacity of the first cycle of the lithium-ion secondary battery. Perform charge and discharge cycles on the lithium-ion secondary battery according to the above method, and record the discharge capacity of each cycle until the discharge capacity of the lithium-ion secondary battery decays to 80% of the discharge capacity of the first cycle, and record the number of charge and discharge cycles.

[0065] Rate performance test: At 25°C, the lithium-ion secondary battery is charged to 4.3V at a constant current of 0.2C, then charged at a constant voltage until the current is less than or equal to 0.05C, then discharged at a constant current of 0.2C to 3.0V, and the discharge capacity at the 0.2C rate is recorded; at 25°C, the lithium-ion secondary battery is charged to 4.3V at a constant current of 0.2C, then charged at a constant voltage until the current is less than or equal to 0.05C, then discharged at a constant current of 2C to 3.0V, and the discharge capacity at the 2C rate is recorded. Lithium-ion secondary battery 2C rate discharge capacity retention rate (%) = 2C rate discharge capacity / 0.2C rate discharge capacity × 100%.

[0066] Example 1

[0067] Preparation of positive electrode sheets: The first positive electrode active material LiMn2O4, the second positive electrode lithium supplement material LiMnO2, the binder PVDF and the conductive carbon black are mixed, wherein the weight ratio of LiMn2O4, LiMnO2, PVDF and the conductive carbon black is 92.5:4.0:1.5:2.0, and the solvent NMP is added at a material-liquid ratio of 7:3, and stirred under vacuum stirring to a uniform transparent system to obtain a positive electrode slurry; the positive electrode slurry is evenly coated on the positive electrode collector aluminum foil, and then transferred to an oven for drying at a drying temperature of 120°C, and then cold pressed and cut to obtain a positive electrode sheet, the weight percentage of the first positive electrode active material LiMn2O4 in the positive electrode active material layer is 92.5%, and the weight percentage of the second positive electrode lithium supplement material LiMnO2 in the positive electrode active material layer is 4.0%.

[0068] Preparation of negative electrode sheets: Mix the negative electrode active material artificial graphite, thickener sodium carboxymethyl cellulose (CMC), binder (SBR) and conductive carbon black in a mass ratio of 95.7:1.0:1.8:1.5, add solvent deionized water in a solid-liquid ratio of 4:6, and obtain negative electrode slurry under the action of a vacuum mixer; evenly coat the negative electrode slurry on the negative electrode collector copper foil; then transfer to an oven for drying at a drying temperature of 120°C, and then cold press and cut to obtain negative electrode sheets.

[0069] Preparation of electrolyte: Ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) are mixed in a volume ratio of 1:1:1 to obtain an organic solvent; LiPF6 is dissolved in the above organic solvent to make the LiPF6 concentration 1 mol / L; based on the total mass of the electrolyte, 3 weight% of vinylene carbonate and 3 weight% of 1,3-propane sultone are added and mixed to obtain an electrolyte.

[0070] Preparation of lithium-ion secondary batteries: The positive electrode sheet, the separator and the negative electrode sheet are stacked at one time. The separator adopts a polypropylene (PP) film with a thickness of 14μm (provided by Celgard), which is located between the positive electrode sheet and the negative electrode sheet to play an isolating role. Then, they are wound into electrode assemblies, the pole ears are welded, and the electrode assemblies are placed in a casing. The electrolyte is injected and sealed. After that, the lithium-ion secondary battery is obtained through standing, forming, shaping and other processes.

[0071] Embodiments 2 to 27

[0072] Different from Example 1, the material components in the positive electrode and the relevant parameters in the preparation steps are adjusted, as shown in Table 1 (in this table, the weight percentage of the first positive electrode active material refers to the weight percentage of the first positive electrode active material in the positive electrode active material, and the weight percentage of the second positive electrode lithium replenishing material refers to the weight percentage of the second positive electrode lithium replenishing material in the positive electrode active material).

[0073] Comparative Example 1

[0074] Different from Example 1, the positive electrode contains only LiMn2O4.

[0075] Comparative Example 2

[0076] Different from Example 1, the positive electrode contains only LiMnO2.

[0077] Comparative Examples 3-4

[0078] Different from Example 1, the weight ratio of the first positive electrode active material and the second positive electrode lithium supplementing material in the positive electrode is different.

[0079] Comparative Examples 5-6

[0080] Different from Example 1, the film resistance, compaction density and single-sided surface density of the positive electrode sheet are different.

[0081] Comparative Examples 7 to 8

[0082] Different from Example 1, the weight percentages of vinylene carbonate and 1,3-propane sultone in the electrolyte are different.

[0083] Comparative Examples 9 to 10

[0084] Different from Example 26, the electrolyte contains only vinylene carbonate or 1,3-propane sultone.

[0085] In each embodiment and comparative example, except for Example 18 in which the contents of conductive carbon black and binder PVDF in the positive electrode active material are 0.5wt% respectively, in other embodiments and comparative examples, the content of conductive carbon black in the positive electrode active material is 2.0wt%, and the content of binder PVDF is 1.5wt%.

[0086] According to the aforementioned method, the high temperature cycle performance and rate performance of the lithium ion secondary batteries obtained in the embodiments and comparative examples were tested. The results are shown in Table 2.

[0087] Table 1

[0088]

[0089]

[0090] Table 2

[0091]

[0092]

[0093]

[0094] It can be seen from the above embodiments and comparative examples that (1) the first positive electrode active material and the second positive electrode lithium supplement material in the present application are used together to produce a synergistic effect. On the one hand, the second positive electrode lithium supplement material used in the present application has a small amount of free lithium on the surface, and when it is added to the positive electrode, the resulting slurry has good stability and excellent processing performance; on the other hand, the second positive electrode lithium supplement material used in the present application has a high first charge specific capacity and a low first coulomb efficiency, which can better compensate for the loss of active lithium caused by the formation of SEI, and more lithium ions are embedded back into the lattice of the first positive electrode active material during discharge, effectively improving the energy density of the lithium ion secondary battery; on the third hand, the first positive electrode active material has a stable structure and good cycle stability, and by controlling the film resistance R, compaction density P and single-sided surface density Q of the positive electrode sheet within the scope of the present application, the lithium ion secondary battery can have good cycle performance and rate performance. (2) The lithium replenishment strategy of the vinylene carbonate added in the electrolyte and the first positive electrode active material and the second lithium replenishment active material can play a synergistic role. During the first charge, a large amount of active lithium released from the second positive electrode lithium replenishment material is embedded in the negative electrode, resulting in a further decrease in the real potential of the negative electrode, causing continuous reduction of the solvent in the electrolyte, affecting the cycle performance. The use of the vinylene carbonate additive within the scope of the present application can induce the formation of a denser and thinner SEI layer, thereby preventing the continuous consumption of the electrolyte. In addition, the electrolyte is also added with a 1,3-propane sultone additive, which can form an interface protection layer on the surface of the positive electrode active material, further improving the cycle performance.

[0095] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present application rather than to limit the scope of protection of the present application. Although the present application has been described in detail with reference to the preferred embodiments, ordinary technicians in this field should understand that the technical solution of the present application can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present application.

Claims

1. A positive electrode sheet, characterized in that: It includes a positive current collector and a positive active material layer provided on at least one surface of the positive current collector. The positive active material layer includes a first positive active material and a second positive lithium supplement material; the positive electrode sheet satisfies 3 ≤ R·P / Q ≤ 15, where R is the resistance of the positive electrode sheet in Ω; P is the tap density of the positive electrode sheet in g / cm 3 ; Q is the single-sided areal density of the positive electrode sheet in g / 1540.25mm 2 ; the first positive active material is Li 1+x Mn y M 2-y O 4-t A t , where -0.1 < x < 0.2, 1 < y ≤ 2, 0 ≤ t < 0.5, M is at least one of Ni, Fe, Zn, Mg, Al, Ti, Zr; A is at least one of S, N, F, Cl, Br; the second positive lithium supplement material is Li 1+r Mn 1-p N p O 2-s B s , where -0.1 < r < 0.2, 0 ≤ p < 0.2, 0 ≤ s < 0.2, N is at least one of Fe, Co, Ni, Ti, Zn, Mg, Al, V, Cr, Zr; B is at least one of S, N, F, Cl, Br.

2. The positive electrode sheet according to claim 1, characterized in that: Satisfy at least one of the following characteristics: (a) R≤5Ω; (b) The P satisfies 2.5 g / cm 3 <P<3.2 g / cm 3 ; (c) Q satisfies 0.3g / 1540.25mm 2 <Q<0.55g / 1540.25mm 2 .

3. The positive electrode sheet according to claim 1, characterized in that: The weight ratio of the first positive electrode active material to the second positive electrode lithium supplement material is 5:1 to 99:

1.

4. The positive electrode sheet according to claim 3, characterized in that: The weight ratio of the first positive electrode active material to the second positive electrode lithium supplement material is 9:1 to 99:

1.

5. The positive electrode sheet according to claim 1, characterized in that: The weight content of the first positive electrode active material in the positive electrode active material is 80% to 98%.

6. The positive electrode sheet according to claim 5, characterized in that: The weight content of the first positive electrode active material in the positive electrode active material is 85% to 98%.

7. A lithium ion secondary battery, characterized in that: It comprises a positive electrode sheet, a negative electrode sheet, a separator and an electrolyte, wherein the positive electrode sheet is the positive electrode sheet as described in any one of claims 1 to 5.

8. The lithium ion secondary battery according to claim 7, characterized in that The electrolyte comprises the following components in percentage by weight: 0.001% to 5% of vinylene carbonate, and / or 0.001% to 5% of 1,3-propane sultone.

Citation Information

Patent Citations

  • Rechargeable lithium battery and negative electrode and positive electrode

    CN101877417A

  • Lithium ion battery anode film, preparation and application thereof

    CN104037418A

  • Dispersion of lithium metal in anode of secondarycell

    CN1427490A

  • Positive electrode piece and lithium ion secondary battery

    CN110265627A

  • Positive pole sheet and sodium-ion battery

    CN110660959A